The good the bad & ugly of food safety: from molecules to mirobes - Abu Bakar, Fatimah (Universiti Putra Malaysia Press, 2012)
Food safety is about ensuring that our food is safe to eat. Food quality concerns ensuring that it is nutritious and acceptable. Food safety is the absolute priority. It must be assured to protect the consumer, and to maintain and expand food markets. Like all disease, foodborne illness seems to strike at random. When people are exposed to foodborne microbes, some of them get sick while many others will suffer few or no ill effects. Foodborne diseases are largely preventable, though there is no simple one-step prevention measure like a vaccine. Instead, measures are needed to prevent or limit contamination all the way from the farm to the table. • A variety of good agricultural and manufacturing practices can reduce the spread of microbes among animals and prevent the contamination of foods. • Careful review of the whole food production process can identify the principal hazards, and the control points where contamination can be prevented, limited, or eliminated. • A formal method for evaluating the control of risk in foods exists is called the Hazard Analysis Critical Control Point, or HACCP system. This was first developed by NASA to make sure that the food eaten by astronauts was safe. HACCP safety principles are now being applied to an increasing spectrum of foods, including meat, poultry, and seafood. For some particularly risky foods, even the most careful hygiene and sanitation are insufficient to prevent contamination, and a definitive microbe-killing step must be included in the process. The main concern is the safety hazards associated with the poultry and aquaculture food animals especially bacterial pathogens. Currently, the most fail-safe method is to consistently monitor the bacterial level in the food animals from the point immediately after obtaining them to just before it is sold to the consumer. However, this has done very little to reduce food poisoning among consumers, as it is time-consuming and lacks reinforcement in some improvised areas of the world. Therefore, research is ongoing worldwide on finding a way to reduce, if not, remove the hazards present in the food animals, either by prevention (before or during its growth), or production. This publication discusses the importance of food safety. It analyzes issues related to food safety, such as spoilage, food-borne pathogens and the microbiological quality of food including some of the examples of work carried out by our research group. It then discusses the significance of contaminants such as biogenic amines with regards to food safety during handling and storage. Our findings provide significant information regarding histamine degrading bacteria and factors influencing its activity. In addition, the findings also emphasized the effectiveness of using bacteria with amines oxidase activity in reducing histamine accumulation in fermented food products. Lastly, the publication looks at the development of rapid enzyme-based biosensor technology in detecting histamine and formaldehyde in fish and seafoods.